2018
DOI: 10.3390/app8112144
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Hydrodynamic-Based Obstacle Avoidance System for Non-holonomic Mobile Robots with Curvature Constraints

Abstract: The harmonic potential field of an incompressible nonviscous fluid governed by the Laplace’s Equation has shown its potential for being beneficial to autonomous unmanned vehicles to generate smooth, natural-looking, and predictable paths for obstacle avoidance. The streamlines generated by the boundary value problem of the Laplace’s Equation have explicit, easily computable, or analytic vector fields as the path tangent or robot heading specification without the waypoints and higher order path characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It controls the relative speed of the pursuer with respect to the evader, depending on the distance between them. Kuo et al [57] showed an obstacle avoidance approach based on velocity potential function. They focused on curvature constraints for a mobile robot.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%
“…It controls the relative speed of the pursuer with respect to the evader, depending on the distance between them. Kuo et al [57] showed an obstacle avoidance approach based on velocity potential function. They focused on curvature constraints for a mobile robot.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%
“…By fully considering the nonholonomic constraints of mobile robot systems, Yuan et al [44] proposed a new quadrupole potential field method to plan collision-free trajectories. Kuo et al [45] implemented a kind of obstacle avoidance method focusing on curvature constraint for a nonholonomic mobile robot. It treated the robot as a particle and adopted the curvature constraint streamline and pure tracking streamline change method.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the obstacles are static which allows a mobile robot to detect obstacles with good accuracy. Researches focus on low cost vision sensors (Feng & Feng, 2017 and multi ultrasonic sensors (Chen et al, 2018, Kuo et al, 2018, Moussa et al, 2018. In a recent research study, low cost sensors including sonars, laser range finder and vision cameras are integrated (Pu et al, 2018) to generate efficient sensor network.…”
Section: Introductionmentioning
confidence: 99%